MOTIVATIONAL FOUNDATIONS AND EXPLICATIVE STRATEGIES OF ASPECTUAL CATEGORIES: A CONCEPTUAL ANALYSIS BASED ON ENGLISH AND UZBEK DATA - Rahmonova Ozoda Sayfillo qizi (World Scientific Research Journal, 2025)
Abstract: This paper investigates the motivational establishments and explicative methodologies of aspectual categories in English and Uzbek. It analyzes how syntactic and lexical angles are conceptualized, communicated, and deciphered in both dialects. The inquiry receives a comparative and cognitive-linguistic approach, analyzing the part of morphological, syntactic, and down-to-earth highlights in forming aspectual implications. The discoveries contribute to an improved understanding of aspectual refinements and their suggestions for linguistic typology and dialect learning.